2014
DOI: 10.1002/pros.22930
|View full text |Cite
|
Sign up to set email alerts
|

The beta-3 adrenoceptor agonist, mirabegron relaxes isolated prostate from human and rabbit: New therapeutic indication?

Abstract: Mirabegron relaxes prostatic smooth muscle, providing an experimental support for the clinical investigation of its combination with an α1-blockers or PDE5 inhibitors in the treatment of BPH. Prostate 75:440-447, 2015. © 2014 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 26 publications
4
22
0
1
Order By: Relevance
“…β2 and β3‐adrenoceptor subtypes are present in prostatic tissues . In the present study, the non‐selective β‐adrenoceptor agonist isoproterenol produced lower relaxations and cAMP levels in prostates from middle‐aged rats, suggesting an impairment of this pathway.…”
Section: Discussionsupporting
confidence: 44%
“…β2 and β3‐adrenoceptor subtypes are present in prostatic tissues . In the present study, the non‐selective β‐adrenoceptor agonist isoproterenol produced lower relaxations and cAMP levels in prostates from middle‐aged rats, suggesting an impairment of this pathway.…”
Section: Discussionsupporting
confidence: 44%
“…Haynes showed that β 2 ‐ and β 3 ‐AR agonists are effective inhibitors of phenylephrine‐induced effects in human cultured prostatic stromal cells and in prostatic tissue . Recently, in human and rabbit prostate, Calmasini et al demonstrated that the β 3 ‐AR agonist mirabegron produced concentration‐dependent relaxation against phenylephrine‐induced contraction . Our study focused on the pharmacological function of β 3 ‐AR in human prostate, and TRK‐380 exerted relaxant effects on KCl‐ and EFS‐induced contractions of the isolated normal human prostate.…”
Section: Discussionmentioning
confidence: 81%
“…22 In animal models of detrusor overactivity such as chronic deprivation of nitric oxide by long-term treatment with L-NAME, 24 hypoxia through the iliac artery injury, 10 and renovascular hypertension, 25 the relaxation induced by β-AR agonists was reduced leading the authors to conclude that the detrusor overactivity seen in these models could be in part due to impairment of the beta-adrenoceptor pathway. In addition to the relaxation in human bladder, 12 mirabegron also relaxed human and rabbit prostatic smooth muscle, 7 suggesting that this drug may be also effective in treating OAB secondary to BPH. To the best of our knowledge, we showed for the first time that the basal levels of cAMP was decreased in bladder from obese mice, thus implying that, together with the greater contractile response to CCh and KCl, lower intracellular levels of cAMP also contributes to the hypercontractile state seen in obese animals.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of beta‐adrenoceptor (β‐AR) in the lower urinary tract organs as bladder and prostate leads to smooth muscle relaxation. Pre‐clinical studies in rat, monkey, and human showed that β3‐AR agonist, mirabegron caused effective relaxation of isolated detrusor smooth muscle (DSM) pre‐contracted with muscarinic agonist, carbachol, or potassium chloride.…”
Section: Introductionmentioning
confidence: 99%